2014
DOI: 10.1111/age.12252
|View full text |Cite
|
Sign up to set email alerts
|

Detecting signatures of selection in nine distinct lines of broiler chickens

Abstract: Modern commercial chickens have been bred for one of two specific purposes: meat production (broilers) or egg production (layers). This has led to large phenotypic changes, so that the genomic signatures of selection may be detectable using statistical techniques. Genetic differentiation between nine distinct broiler lines was calculated using Weir and Cockerham's pairwise FST estimator for 11 003 genome-wide markers to identify regions showing evidence of differential selection across lines. Differentiation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Recent advances in genomic technologies resulting in the availability of the Illumina Goat 50K SNP BeadChip [6] have offered the opportunity to search for genomic regions that may have undergone selection. Such studies in cattle [79], sheep [10, 11], chickens [12] and pigs [13, 14] have each identified genes that have undergone positive selection and are likely to contribute directly to phenotypic variation. However, in goats there are only a few studies using the SNP arrays and most of them focused on local breeds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in genomic technologies resulting in the availability of the Illumina Goat 50K SNP BeadChip [6] have offered the opportunity to search for genomic regions that may have undergone selection. Such studies in cattle [79], sheep [10, 11], chickens [12] and pigs [13, 14] have each identified genes that have undergone positive selection and are likely to contribute directly to phenotypic variation. However, in goats there are only a few studies using the SNP arrays and most of them focused on local breeds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“… (G) Study of commercial broiler lines (Stainton et al . ). Includes regions showing statistically significant between‐line differentiation (Table ). …”
Section: Discussionmentioning
confidence: 97%
“…In our previous study of nine broiler chicken lines (including line 3, analysed in the current study) genotyped using a low‐density SNP chip, a number of highly differentiated regions were identified in multiple lines (Stainton et al . ). Eight of the 15 regression regions were located within 1 Mb of the highly differentiated regions (Table ), consistent with the theoretical expectation of negative relationship between diversity and F ST (Charlesworth ; Cruickshank & Hahn ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations